2015
DOI: 10.1002/anie.201501414
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Charge‐Transfer Interactions in Self‐Assembled Organic Cocrystals: Two‐Dimensional Photonic Applications

Abstract: A new crystal of a charge-transfer (CT) complex was prepared through supramolecular assembly and it has unique two-dimensional (2D) morphology. The CT nature of the ground and excited states of this new Bpe-TCNB cocrystal (BTC) were confirmed by electron spin resonance measurements, spectroscopic studies, and theoretical calculations, thus providing a comprehensive understanding of the CT interactions in organic donor-acceptor systems. And the lowest CT1 excitons are responsible for the efficient photoluminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
164
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(186 citation statements)
references
References 45 publications
20
164
0
2
Order By: Relevance
“…Although co-crystals of APIs are not going to be a panacea [for example, it seems unlikely that they will, in general, be any less prone to polymorphism than are homomeric molecular solids (Aitipamula et al, 2014)], they will likely offer useful strategies and opportunities that can facilitate the development of new drugs and formulations for the future. Similar progress can be expected in areas related to agrochemicals (George et al, 2013), nutraceuticals (Schultheiss et al, 2010), liquid crystals (Nguyen et al, 2004), charge-transfer (Zhu et al, 2015) and non-linear optical materials (Gryl et al, 2015), to name but a few.…”
Section: Applications Of Co-crystals and Co-crystal Technologysupporting
confidence: 55%
“…Although co-crystals of APIs are not going to be a panacea [for example, it seems unlikely that they will, in general, be any less prone to polymorphism than are homomeric molecular solids (Aitipamula et al, 2014)], they will likely offer useful strategies and opportunities that can facilitate the development of new drugs and formulations for the future. Similar progress can be expected in areas related to agrochemicals (George et al, 2013), nutraceuticals (Schultheiss et al, 2010), liquid crystals (Nguyen et al, 2004), charge-transfer (Zhu et al, 2015) and non-linear optical materials (Gryl et al, 2015), to name but a few.…”
Section: Applications Of Co-crystals and Co-crystal Technologysupporting
confidence: 55%
“…In contrast the notorious aggregation-caused quenching (ACQ), branchy and twisted aggregation-induced emission (AIE) and aggregation-induced emission enhancement (AIEE) fluorogens are developed to tune the intermolecular stacking for efficient emissions in the solid state29303132. Alternative ways to regulate multifunctional materials are allomorphism and mischcrystal333435. This strategy do not involves tedious organic synthesis.…”
mentioning
confidence: 99%
“…A puzzle we are encountering is to distinguish the ground and excited state [36,37]. Recently, we [38] found that both of ground and excited states of 1,2,4,5-tetracyanobenzene (TCNB) based cocrystals are actually CT state, as experimentally verified by spectroscopic studies, electron spin resonance (ESR) measurements and theoretical calculations (Fig. 2).…”
Section: Science China Materialsmentioning
confidence: 85%